2016
DOI: 10.1001/jamapsychiatry.2016.1134
|View full text |Cite
|
Sign up to set email alerts
|

The Salience of Reward

Abstract: An important and so far minimally addressed aspect of psychosis research is the manifestation of genetic psychosis susceptibility, as measured with polygenic risk profile scores (RPSs), on human brain function. The study of more than 1500 adolescents by Lancaster et al 1 in this issue of JAMA Psychiatry reveals that the genetic vulnerability to developing psychosis is associated with increased brain activity in the ventral striatum during reward processing. This finding suggests that the genetic risk of psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
(25 reference statements)
0
9
0
Order By: Relevance
“… 43 They may also reflect developmental differences: a recent study of over 1500 adolescents found reward-related responses in the ventral striatum increased with increased polygenic psychosis risk scores. 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
“… 43 They may also reflect developmental differences: a recent study of over 1500 adolescents found reward-related responses in the ventral striatum increased with increased polygenic psychosis risk scores. 46 , 47 …”
Section: Discussionmentioning
confidence: 99%
“…26 A similar approach has been employed in previous studies on stress reactivity 27 and in previous studies examining emotional processing in cannabis users. 19,20,28,29 Exclusion criteria included (1) age < 18 or > 40 years, (2) left-handedness, (3) history or current DSM-IV axis I disorders (based on MINI, exception: cannabis abuse or dependence), (4) Beck Depression Inventory (BDI-II) score > 20 30 , (5) current or history of a medical disorder including endocrinological abnormalities (6) current or regular use of medication, (7) usage of other illicit substances > 75 lifetime occasions or during the 28 days prior to the experiment, (8) positive urine screen for cocaine (300 ng/ml), methamphetamine (500 ng/ml), amphetamine (500 ng/m), methadone (300 ng/ml) or opiate (300 ng/ml) (Drug-Screen-Multi 7TF, von minden GmbH, Moers, Germany), (9) breath alcohol >0.00% (analyzed using TM-7500, Trendmedic, Penzberg, Germany). For controls, additional exclusion criteria were applied: (1) cumulative lifetime use of cannabis > 15 g (M = 1.29, SD = 1.02), (2) use of any other illicit substance >10 lifetime occasions.…”
Section: Methodsmentioning
confidence: 99%
“…3 Cannabis use-associated alterations in the domains of reward processing and cognition have been extensively studied 4,5 and there is growing evidence from functional imaging studies suggesting neuroplastic adaptations in neural systems subserving these functions. 6,7 In the cognitive domain, selective impairments in attention, working and associative memory have been reported most consistently. 4,5,8,9 Long-term stress has detrimental effects on mental health 10 and the acute stress response is an adaptive mechanism to environmental demands that are perceived as potentially threatening.…”
Section: Introductionmentioning
confidence: 99%
“…26 A similar approach has been used in previous studies on stress reactivity 27 and in studies examining emotional processing in cannabis users. 19,20,28,29 Exclusion criteria included (1) age younger than 18 or older than 40 years; (2) left-handedness; (3) history or current DSM-IV axis I disorder (based on MINI; exception: cannabis abuse or depend ence); (4) Beck Depression Inventory (BDI-II) score greater than 20; 30 (5) current or history of a medical disorder, including endocrinological abnormalities; (6) current or regular use of medication; (7) use of other illicit substances on more than 75 lifetime occasions or during the 28 days before the experiment; (8) positive urine screen for cocaine (300 ng/mL), methamphetamine (500 ng/mL), amphetamine (500 ng/mL), methadone (300 ng/mL) or opiate (300 ng/mL; Drug-Screen-Multi 7TF, von minden GmbH, Moers, Germany); (9) breath alcohol > 0.00% (analyzed using TM-7500, Trendmedic, Penzberg, Germany). For controls, additional exclusion criteria were applied: cumulative lifetime use of cannabis > 15 g (mean ± standard deviation [SD] 1.29 ± 1.02); use of any other illicit substance on more than 10 lifetime occasions.…”
Section: Participantsmentioning
confidence: 99%
“…3 Cannabis use-associated alterations in the domains of reward processing and cognition have been extensively studied, 4,5 and there is growing evidence from functional imaging studies suggesting neuroplastic adaptations in neural systems that subserve these functions. 6,7 In the cognitive domain, selective impairments in attention and working and associative memory have been reported most consistently. 4,5,8,9 Long-term stress has detrimental effects on mental health, 10 and the acute stress response is an adaptive mechanism to environmental demands that are perceived as potentially threatening.…”
Section: Introductionmentioning
confidence: 99%